The occurrence of the bovine mastitis in the "dairy belt" of Rio de Janeiro - Langenegger, Jerome; Coelho, Nilton Martins; Langenegger, Charlotte Hubinger; Castro, Raul Pimenta de (Pesquisa Agropecuaria Brasileira, 2014)
2.187 lactating cows from 43 farms in 25 districts of the "dairy belt" around Rio de Janeiro were examined. The clinical exploration of the udders showed that 101 quarters of 87 cows (4%) were affected by acute or chronic mastitis. Hundred and forty one cows (7%) had 167 dry quarters. The California mastitis test has shown in 429 cows (20%) some disturbance of milk samples of these cows were isolated: Streptococcus agalactiae in 106 (24.7%); Str. dysgalactiae in 74 (17.2%); Str. uberis in 20 (4.6%); Staphylococcus aureus in 227 (53.1%); Corynebacterium pyogenes in 18 (4.2%); Pasteurella multocida in 4 (0.9%) and Escherichia coli in 2 (0.4%). No mastitis was detected in 12 farms and in 11 cases only one species of microorganism was found; in the others 2 to 5 species were identified.